2019
DOI: 10.1149/2.1081914jes
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Detection of Chikungunya Non-Structural Protein 3 Using Electrochemical Impedance Spectroscopy

Abstract: Chikungunya is a mosquito-borne infectious disease, which causes acute fever and joint pain, and can trigger long term arthritis.In the present study, we demonstrate a label-free detection of chikungunya virus non-structural protein 3 (CHIKV-nsP3), which is responsible for alphavirus replication, using electrochemical impedance spectroscopy (EIS). This is hitherto, the first work addressing the detection of CHIKV-nsP3 using biosensors. The immunosensors were developed by modifying a gold surface using self-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In recent years, electrochemical biosensor has become a reliable analytical equipment [ [146] , [147] , [148] ], which can detect various viruses that threaten human health [ [149] , [150] , [151] ]. Electrochemical biosensor is a kind of equipment which has both electrochemical sensing and biosensor [ 152 , 153 ].…”
Section: Detection Methodsmentioning
confidence: 99%
“…In recent years, electrochemical biosensor has become a reliable analytical equipment [ [146] , [147] , [148] ], which can detect various viruses that threaten human health [ [149] , [150] , [151] ]. Electrochemical biosensor is a kind of equipment which has both electrochemical sensing and biosensor [ 152 , 153 ].…”
Section: Detection Methodsmentioning
confidence: 99%
“…SAM was activated by N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hy-drochloride (EDC) and N-hydroxysuccinimide (NHS) to form NHS ester. As a result, impedance decrease effectively ( George et al, 2019 ). It should not be left unmentioned that the study is consistent with previously reported literature ( Radhakrishnan et al, 2016 ).…”
Section: Electrochemical Biosensors For Virus Detectionmentioning
confidence: 99%
“…In addition, commercial immunochromatography antigen detection kits are gaining popularity in the recent past owing to their high sensitivity and specificity with no cross-reactivity with other arboviruses ( Okabayashi et al, 2015 ; Jain et al, 2018a ). Other diagnostic initiatives are the use of biosensors using different technologies such as electrochemical impedance spectrometry and optical fibers that have shown promise in CHIKV diagnosis ( George et al, 2019 , 2021 ).…”
Section: Laboratory Diagnosismentioning
confidence: 99%